Eficácia do cimento de ionômero de vidro como selante oclusal sobre a paralisação de lesões cariosas em dentina - Silveira, Ana Daniela Silva da (2007)
Dental caries consists in a multifactorial and dynamic process. The knowledge of the ionic interactions among dental tissues and dental biofilm make possible its understanding as a process that can be stopped. Recently, the use of sealants have lost its function as preventive agent and passed to be argued as a possible therapeutical agent. This happens by hindering the substratum flow to the lesion inner and, therefore, controls the advance of the process. This study aimed to evaluate glass ionomer cement as a not invasive technique of treatment in occlusal caries without clinical cavitation, but with dentinal involvement. The research was accomplished using a controlled clinical trial with two groups (experimental and control) in 38 subjects (8-18 years) with 51 molars. The teeth of the experimental group were sealed with glass ionomer cement (Vidrion-R, S.S.White, Juiz de Fora, Brazil) and the molars control did not suffer intervention. The experimental group was followed by a year and the control by 8 months due the progression of the carious injury. Both groups were reevaluated to each 4 months with the use of clinical, radiographic and laser fluorescence (DIAGNOdent®) examination. The analysis of the clinical evaluation did not observe a significant difference between experimental and control groups. However, analysis with radiographic and laser fluorescence (DIAGNOdent®) examination observed a significant difference (p> 0,05) between groups, demonstrating a wors condition to the group without intervention. The results suggest that glass ionomer cement as sealant can be efficient to paralyze dentinal caries without clinical cavitation